Profil Penggunaan Obat Diare pada Berbagai Kelompok Usia di Klinik Akmil Magelang: Profile of Diarrhea Medication Use Across Age Groups at the Military Academy Medical Center in Magelang - Sakti, Diwang Ningsih Endang; Santoso, Setiyo Budi; Dianita, Puspita Septie (Department of Pharmacy, Bumigora University, 2025)
The prevalence of diarrhea is widespread in developing countries and is a leading cause of global morbidity and mortality. This article presents a profile of medication use in the management of diarrhea based on age groups. The study utilized a quantitative approach by analyzing 123 prescriptions from diarrhea patients at the Military Academy Health Clinic in Magelang during 2021. Data were analyzed using frequency distribution tabulations with Microsoft Excel 2016. The results indicate that antidiarrheal prescriptions are age-adjusted, probiotics are the primary choice for infants and children, while loperamide is recommended for adolescents to the elderly. Adsorbents serve as an alternative across all age groups. Management of older patients also considers prognosis and accompanying symptoms, which includes antibiotics, antiulcer medications, and antispasmodics. Supportive therapies such as zinc supplementation and oral rehydration are applied across all age categories.